TOWARDS PROSPEROUS HOUSING: CONSTRUCTION of An ISLAMIC HOUSING CONCEPT WITH A HAYATAN THAYYIBAH PERSPECTIVE - Santoso, Budiyono; Ahmad Jalaluddin; Aunur Rofiq (Multifinance, 2024)
Welfare studies are still dominated by materialistic aspects of welfare theory and deny spiritual aspects and spiritual elements. Even though the spiritual aspect is an important thing that influences human life in all aspects. This research aims to explore and develop a concept/model of welfare in housing which was developed based on the Islamic welfare perspective Hayatan Tayyibah. The concept of living well-being Thayyibah is explored using a phenomenological approach, which is a form of design methodology developed based on the Islamic paradigm. Data mining uses interview, observation, and documentation methods. The informants consisted of knowledgeable and experienced informants Data analysis was carried out by describing textural meaning and structural meaning, then carrying out a synthesis to create a universal description of the phenomenon under study. The research findings conclude that the construction of welfare in Islamic housing is referred to as "prime prosperity". This welfare consists of three main aspects: personal, social environment, and housing development companies. The personal aspect highlights the individual's physical and mental conditions, including physical and spiritual dimensions. The social environment is related to comfort, health, and social relationships in housing, while the housing developer aspect emphasizes the business conditions and environment of the developer company. In other words, this research not only assesses welfare from an individual perspective but also considers social and corporate aspects of welfare construction Islamic housing context.